2019
DOI: 10.1108/ecam-02-2019-0079
|View full text |Cite
|
Sign up to set email alerts
|

Integrated priority decision index for risk assessment in chaos: cost overruns in transport projects

Abstract: Purpose Cost overrun is inherent to project chaos, which is one of the key drivers of project failure. The purpose of this paper is to explore the critical elements of complexity-risk interdependency for cost-chaos in the construction management domain by utilizing a multi-criteria decision model. Design/methodology/approach A total of 12 complexity and 60 risk attributes are initially identified from the literature and using expert’s judgements. For the development of a structured hierarchy of key complexit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 78 publications
(177 reference statements)
0
14
0
Order By: Relevance
“…As Pakistan is considered as a dynamic market in which risks and returns assessments from an investor’s point of view is a great and rapidly evolving challenge. Therefore, due to the consistent changes in markets, nothing is identical neither the stocks nor the future foretells (Afzal et al , 2019b). In such swapping conditions of dynamic markets where the returns have too much variations, traditional methods like averages and means do not provide a true picture of market (Afzal et al , 2021).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…As Pakistan is considered as a dynamic market in which risks and returns assessments from an investor’s point of view is a great and rapidly evolving challenge. Therefore, due to the consistent changes in markets, nothing is identical neither the stocks nor the future foretells (Afzal et al , 2019b). In such swapping conditions of dynamic markets where the returns have too much variations, traditional methods like averages and means do not provide a true picture of market (Afzal et al , 2021).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Numerous studies have identified poor contract management as one of the critical causes of cost overrun (Alinaitwe et al. , 2013; Afzal et al. , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The first stage of synthesizing the 152 literatures is dividing them according to 2 classifications, literatures from the developed countries and literatures from developing countries as presented in Table 2 & 3. (Afzal et al, 2019;Anish et al, 2019;Bhangale, 2016;Chandramohan et al, 2012;Cindrela Devi & Ananthanarayanan, 2017;Ghumare et al, 2019;Kant, 2018;Muthu Venkata Sekar & Mahalakshmi, 2018;Pai et al, 2018;Raju et al, 2017;Shaktawat & Vadhera, 2017;Shanmuganathan & Baskar, 2015;Sharma et al, 2020;Sharma & Goyal, 2019;Shrivastava et al, 2019;Subramani & Sivakumar, 2018;Velumani & Nampoothiri, 2019;Venkateswaran & Murugasan, 2017;Wanjari & Dobariya, 2016) Malaysia 20 (Abdullah et al, 2018;Afzal et al, 2019;Akram et al, 2017;Asmi et al, 2013;Azis et al, 2013;Hameed Memon et al, 2014;Haslinda et al, 2018;Ismail et al, 2013;Karunakaran et al, 2018;Liew et al, 2019;Memon et al, 2011Memon et al, , 2012Rahman et al, 2013;C. Ramanathan et al, 2012;C.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Ramanathan et al, 2012;C. T. Ramanathan et al, 2011;) Pakistan 9 (Afzal et al, 2019;Akram et al, 2017;Choudhry et al, 2014Choudhry et al, , 2018Choudhry & Rehman Nasir, 2012;Hanif et al, 2016;Maqsoom et al, 2018;Samiullah Sohu et al, 2017;Zafar et al, 2016) China 6 (Afzal et al, 2019;Lou & Yin, 2010;Ma, 2011;Mansur et al, 2019;Wang & Yuan, 2011;Yuanyue & Huimin, 2018) Ghana 5 (Asiedu et al, 2017;Asiedu & Adaku, 2019;Coffie et al, 2019) Nigeria 4 (Akinradewo et al, 2019;Akinsiku et al, 2014;Amadi & Higham, 2019;Amusan et al, 2018;Hingham, 2016) Saudi Arabia 4 (Alghonamy, 2015;Mahamid, 2013Mahamid, , 2018Seddeeq et al, 2019) South Africa 4 (Khabisi, 2012;Monyane et al, 2018;Mulalo et al, 2018 (Jung et al, 2016;Kavuma et al, 2019;Qiao et al, 2019) Vietnam 3 (S. Kim et al, 2017;S. Y. Kim et al, 2018;Pham et al, 2020) Others 21 (Afzal et al, 2019;Al-hazim et al, 2017;Alzebdeh et al, 2015;Apolot & Tindiwensi, 2013;…”
Section: Synthesis Of Resultsmentioning
confidence: 99%